(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The article examines the role of online reviews and user feedback in shaping the image of service companies, as well as their impact on customer trust and loyalty. In the context of digitalization and active use of the Internet, reviews and ratings have become an integral part of the consumer decision-making process. Social platforms and specialized services allow users to exchange opinions on the quality of services, which has a significant impact on the reputation of companies. Particular attention is paid to how organizations can effectively manage reviews, respond to negative comments, and use positive reviews to strengthen their image and increase customer loyalty. The article analyzes the main factors influencing consumer perception of a business and suggests strategies for improving customer interaction through online reviews.